2022
DOI: 10.1017/jns.2022.6
|View full text |Cite
|
Sign up to set email alerts
|

Plant-based meat and dairy substitutes on the Norwegian market: comparing macronutrient content in substitutes with equivalent meat and dairy products

Abstract: Objective: To assess and compare the macronutrient and salt content in meat and dairy substitutes available on the Norwegian market. Design: Comparison between substitute products and two groups of meat and dairy products where one group represented the healthiest option (Keyhole) and one the most used option (Regular). Kruskal–Wallis test with pairwise comparison was conducted on categories with more than two groups, and Mann–Whitney U test was conducted on categories with two groups. Setting: Online stores i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
37
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(52 citation statements)
references
References 32 publications
7
37
0
Order By: Relevance
“…For meat substitutes, daily consumption was low (2%), across all diet groups. A newly published study found that the nutritionally component of dairy and meat substitutes on the Norwegian market vary ( 24 ). In France, a study found ( 25 ) that vegans and vegetarians had poorer diet quality due to higher intake of ultra-processed foods, which plant-based replacements products are often classified as.…”
Section: Discussionmentioning
confidence: 99%
“…For meat substitutes, daily consumption was low (2%), across all diet groups. A newly published study found that the nutritionally component of dairy and meat substitutes on the Norwegian market vary ( 24 ). In France, a study found ( 25 ) that vegans and vegetarians had poorer diet quality due to higher intake of ultra-processed foods, which plant-based replacements products are often classified as.…”
Section: Discussionmentioning
confidence: 99%
“…Data collection followed previous studies on modified versions of commercialized products ( 6 , 23 25 ). Products from the most significant producers were chosen, covering most of the Brazilian market.…”
Section: Methodsmentioning
confidence: 99%
“…The per capita global meat intake is projected to be 35 kg/year ( 5 ). Given the expected population growth and increased influx of low and middle-income countries, the global demand for animal-based products would overcome the world's capacity up to 2,050 ( 6 ). On the other hand, people are concerned about the effects of meat-eating on their health and the environment since plant-based diets have been pointed out as one measure to face climate change and non-communicable diseases ( 5 , 7 ).…”
Section: Introductionmentioning
confidence: 99%
“…For standardiation and comparison purposes, all values were converted to a serving size of 100 g. According to Brazilian legislation, nutritional labels can be based on food composition tables and present a discrepancy level of 20% (for more or less) between its actual chemical composition and that described on the label ( 38 ). Thus, possible divergences may be present, as evidenced by other studies utilizing food labels as their information source ( 9 , 19 , 37 , 39 , 40 ).…”
Section: Methodsmentioning
confidence: 95%
“…Data collection was performed according to previous studies ( 9 , 36 , 37 , 39 , 40 ). The qualitative and quantitative data reported on the products' food labels were recorded, including firm name, brand name, descriptive name, ingredient list, nutrient information, and serving size.…”
Section: Methodsmentioning
confidence: 99%